As transferências governamentais e sua relação com a arrecadação de imposto: uma análise de dados em painel - Duarte, Patricia Mattos (2022)
The purpose of the proposed study is to analyze the effect of government transfers on the own collection of the municipalities of Mato Grosso do Sul, in order to show whether they cause stimulus or discouragement. The configuration of the tax division, provided for in the Federal Constitution of 1988, was created with the objective of equalizing the supply of public goods and services between states and municipalities and reducing regional disparities, given that the tax capacity of some regions of the country is lower. in relation to others. However, these transfers tend to generate a discussed inertia in the effective collection of taxes by the municipalities, making them increasingly dependent on these resources. As a result, it is assumed that this problem tends to worsen in smaller municipalities in terms of population, influenced by the reduced tax base, the political cost to the image of the manager who decides to intensify the collection and inspection of taxes (especially during electoral periods) and also, by the increase in spending, supported by funds received from transfers, generating expenses that become institutionalized, making budget execution reckless in the face of a possible reduction in transfers, which is plausible, given that the basis for calculating these is composed of taxes that fluctuate in collection according to the economic scenario, such as the tax on industrialized products and the income tax. In order to better understand this context, the object of study includes the 79 municipalities in the state of Mato Grosso do Sul with data from the period 2016 to 2020, referring to their own collection, fiscal transfers, SUS resources, FUNDEB, FPM and others. Considering the nature of the data, this information was processed using the panel data method, and analyzed according to the type of effect, fixed or random. As for the proposed method, it is able to capture the different realities and time of the municipalities that are part of the sample. The results indicate a positive situation, in which the municipalities of MS presented, in the delimited period, stimulus of collection in function of the fiscal transfers, revealing that even existing dependence on the resources of the transfers, they do not cause disincentive in the proper collection. In addition, the verified result reveals that there is an effort by municipal managers to seek to sustain themselves. In the meantime, the selected effort can be explained by the higher collection of ITBI and TAXES, in view of an increase in total expenditure, in the same way it occurred with the collection of IPTU, in view of an increase in the FPM.